DISPOSITION EFFECT AMONG BRAZILIAN EQUITY FUND MANAGERS - EDUARDO POZZI LUCCHESI (RAE - Revista de Administração de Empresas, 2015)
The disposition effect predicts that investors tend to sell winning stocks too soon and ride losingstocks too long. Despite the wide range of research evidence about this issue, the reasons that leadinvestors to act this way are still subject to much controversy between rational and behavioral expla-nations. In this article, the main goal was to test two competing behavioral motivations to justify thedisposition effect: prospect theory and mean reversion bias. To achieve it, an analysis of monthlytransactions for a sample of 51 Brazilian equity funds from 2002 to 2008 was conducted and regres-sion models with qualitative dependent variables were estimated in order to set the probability of amanager to realize a capital gain or loss as a function of the stock return. The results brought evidencethat prospect theory seems to guide the decision-making process of the managers, but the hypothesisthat the disposition effect is due to mean reversion bias could not be confirmed.